INHIBITION OF RED CELL SEQUESTRATION BY CORTISONE - Kaplan, Manuel E. (The Rockefeller University Press, 1961)
The effect of cortisone on the sequestration of (a) antibody-coated red cells and (b) incubated red cells was studied in rats. Cortisone administration inhibited the hepatic sequestration of red cells altered by non-immune as well as by immune injury. There was a latent period of 2 days between the institution of cortisone therapy and its first manifest effect on hepatic sequestration. The splenic sequestration of altered red cells was not inhibited by cortisone, and there was no inhibition of the sequestration of hemoglobin by either liver or spleen. It is suggested that steroids may inhibit hepatic sequestration through hemodynamic effects.